Optimalisasi neuroplasticity dan ketangkasan fisik balita melalui latihan brain-gym (Cukat Trengginas) - Santri Raminda; Hikmatul Laili Nur`aini; Fatimah Wahab Aliyun; Zahne Putri Asifa Ramadhani; Andina Risky (JOURNAL of Public Health Concerns, 2026)
Background: Toddlerhood (ages 1–5) is a golden age in child development. During this phase, a child's brain experiences rapid development and is sensitive to environmental stimulation. However, challenges in the modern era indicate a tendency for delays in gross and fine motor development in toddlers. One non-invasive and enjoyable intervention considered effective in bridging this stimulation gap is brain-gym. Purpose: To increase parents' knowledge of optimizing neuroplasticity and physical agility through brain-gym exercises. Method: Physiotherapy activities were conducted on Tuesday, May 12, 2026, from 9:00–11:00 a.m. WIB in Tondomulyo Village, Pati, Central Java. The physiotherapy intervention method used was brain-gym. The activities were conducted using a brain-gym intervention approach. Evaluation was conducted by analyzing pre-test and post-test results, calculating the difference in respondents' average knowledge scores and presenting them descriptively to assess changes in respondents' knowledge levels after the brain-gym intervention was given to parents. Results: The level of knowledge of respondents before the educational activity was 20.0% in the sufficient category and 80.0% in the poor category. Meanwhile, the level of knowledge of respondents after the educational activity was 93.3% in the good category and 6.7% in the sufficient category. Conclusion: This educational activity has proven effective in increasing parents' knowledge and skills regarding Brain-Gym physiotherapy. This activity also has a positive impact on the community, including improved theoretical understanding, practical skills, and behavioral changes for the better. Suggestion: Optimizing neuroplasticity and physical agility in toddlers through Brain-Gym exercises needs to be implemented routinely and continuously, accompanied by periodic evaluations to monitor knowledge and prevent developmental problems in toddlers in the community. Keywords: Brain-Gym; Neuroplasticity; Physiotherapy; Physical agility Pendahuluan: Masa balita (usia 1–5 tahun) merupakan periode golden age atau masa keemasan dalam tumbuh kembang anak. Pada fase ini, otak anak mengalami perkembangan yang sangat masif dan sensitif terhadap stimulasi lingkungan. Namun, tantangan di era modern saat ini menunjukkan adanya kecenderungan keterlambatan perkembangan motorik kasar dan halus pada balita. Salah satu intervensi non-invasif dan menyenangkan yang dinilai efektif untuk menjembatani stimulasi ini adalah brain-gym (senam otak). Tujuan: Meningkatkan pengetahuan orang tua balita terhadap Optimalisasi neuroplasticity dan ketangkasan fisik balita melalui latihan brain-gym. Metode: Kegiatan fisioterapi dilaksanakan pada hari selasa, 12 Mei 2026 pada pukul 09.00-11.00 WIB berlokasi di Desa Tondomulyo, Pati, Jawa Tengah. Menggunakan metode intervensi fisioterapi dengan brain-gym. Kegiatan dilakukan dengan pendekatan intervensi brain-gym. Evaluasi dilakukan dengan menganalisa hasil pre-test dan post-test yaitu menghitung selisih nilai rata-rata pengetahuan responden dan disampaikan secara deskriptif untuk melihat perubahan tingkat pengetahuan responden setelah diberikan intervensi brain-gym kepada orang tua. Hasil: Menunjukkan bahwa tingkat pengetahuan responden sebelum kegiatan edukasi adalah sebanyak 20.0% dalam kategori cukup dan sebanyak 80.0% dalam kategori kurang. Sedangkan tingkat pengetahuan responden setelah kegiatan edukasi menjadi sebanyak 93.3% dalam kategori baik dan sebanyak 6.7% dalam kategori cukup. Simpulan: Kegiatan edukasi ini terbukti efektif meningkatkan pengetahuan dan kemampuan orang tua tentang brain-gym fisioterapi. Kegiatan ini juga memberikan dampak positif pada masyarakat yang meliputi perbaikan pemahaman teori, kemampuan praktik, hingga perubahan perilaku ke arah yang lebih baik. Saran: Optimalisasi neuroplasticity dan ketangkasan fisik balita melalui latihan brain-gym perlu dilaksanakan secara rutin dan berkelanjutan disertai evaluasi berkala guna memantau pengetahuan dan mencegah permasalahan tumbuh kembang balita di masyarakat.